Sensemaking revisited. Issue 5 (November 2014) - Holt, Robin; Cornelissen, Joep
We critique and extend theory on organizational sensemaking around three themes. First, we investigate sense arising non-productively and so beyond any instrumental relationship with things; second, we consider how sense is experienced through mood as well as our cognitive skills of manipulation based on standard categories, frames or narratives and third, we consider sense being governed by exposure to unknown possibility rather than retrospective assessment. We set these themes in the context of the study of Heidegger and discuss the implications of our theorization for further sensemaking research by revisiting Weick's seminal reading of Norman Maclean's book surrounding the tragic events of a 1949 forest fire at Mann Gulch, USA.